BECOMING MAJIKAN IN OUR OWN FARM: A STUDY ON WOMEN AND AGROFORESTRY IN CIANJUR, WEST JAVA - Oekan Soekotjo Abdoellah; Johan Iskandar; Parikesit Parikesit; Dede Tresna Wiyanti (Universitas Padjadjaran, 2023)
This study examines the relation between women and agroforestry in Cijedil and Wangunjaya Villages, Cugenang District, Cianjur Regency, West Java. The study of the dynamics of agroforestry management, which is an agricultural practice carried out on forest land or land that resembles a forest, is carried out using an ecofeminist perspective. The study was conducted in two villages in Cianjur, West Java, Indonesia. These two villages are representatives of agroforestry land variations, which consist of forest, agroforestry, and agricultural land. This land type represents the level of human intervention in forest land management. The research was conducted using quantitative and qualitative research methods, using interviews and observation as key data collection instruments. The results of the study found that the division of labor based on gender in agroforestry practices has changed. Significant changes were also found in the relations between women and agroforestry, as well as gender relations in the decision-making process related to agroforestry in farmer households. From an eco-feminist perspective, this study shows that the dynamics of women in managing agroforestry not only increases the role of women, but also strengthens the position of women as employers in their own agroferestry land.